(untitled) (Lex localis - Journal of Local Self-Government, 2025)
With the emergence of numerous digital platforms, the nature of crime has changed, offering new avenues for and challenges to policing. As criminal actors increasingly turn to online environments for nefarious ends, law enforcement encounters complicated challenges of jurisdiction, legal and technological waters to navigate. Traditional investigative techniques have become less effective in combating cybercrime due to the anonymity of the dark web, the use of encryption, and the borderless landscape of cyberspace. In this article, we will look at the increasing complexity of crime in the digital world, and how this is becoming more of a headache for law enforcement. It further explores the potential to improve crime prevention and the challenges that law enforcement will continue to face as criminals leverage online domains for illegal activities amidst jurisdiction, legal and technological hurdles. The paper also looks at new strategies and innovations among digital tools to improve crime prevention and crime investigation. The study employs doctrinal research, an explicitly descriptive method drawing from digital crime and a due process to digital world theory amidst technology and law enforcement challenges. To sum up, the challenges that arise from digital platforms to fight cybercrime is indeed formidable but not impossible to tackle. But with the right technological tools, as well as international cooperation and legislative reform, law enforcement is well-equipped to handle the challenges of this digital age and to prevent individuals, organizations, and societies from falling victim to the endemic threat of cybercrime.